Hmox1 Deficiency Sensitizes Mice to Peroxynitrite Formation and Diabetic Glomerular Microvascular Injuries. (22nd November 2017) - Lenoir, Olivia; Gaillard, François; Lazareth, Hélène; Robin, Blaise; Tharaux, Pierre-Louis
Abstract : Objective. Indirect evidence suggests a role for heme oxygenase-1 (HO-1) in limiting diabetic vasculopathy. The goal of this study was to assess the role of HO-1 in the development of microvascular lesions within glomeruli during diabetes mellitus using a mouse model with specific alteration of the Hmox1 gene. Approach and Results. The effects of Hmox1 haploinsufficiency were studied as a means of assessing the intrinsic contribution of HO-1 in the development of renal microvascular lesions during diabetes. Renal function and histology were analyzed 10 weeks after diabetes induction with streptozotocin. Diabetic Hmox1 +/− mice showed higher levels of albuminuria and blood urea compared to their wild-type diabetic littermates. More severe glomerular microvascular lesions were also observed in the diabetic Hmox1 +/− mice. This was associated with a renal increase in the expression of the oxidative stress marker, nitrotyrosine. Conclusions. Genetic Hmox1 partial deficiency is sufficient to sensitize mice to the development of diabetic glomerular microvascular lesions. HO-1 exerts antioxidant effects in the kidney during diabetes mellitus. These have protective effects on the development of glomerular endothelial injury.